2009
DOI: 10.1097/paf.0b013e3181873784
|View full text |Cite
|
Sign up to set email alerts
|

Drugs, Detention, and Death

Abstract: It has been theorized that drug abusers recently released from prison have an increased risk of fatal drug overdose. The objective of this study was to determine whether persons released from prison in the state of New Mexico have an increased risk of death due to unintentional drug overdose in the time immediately after release from prison. A total of 96 people were identified who had been released from prison and subsequently suffered an unnatural death in 2001 through 2003. Among those who had drug-caused d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(29 citation statements)
references
References 19 publications
3
26
0
Order By: Relevance
“…Although they have not focused solely on community-sentenced offenders, these studies are helpful to highlight the problem of suicide in this population, as many of these offenders will still be supervised by the probation service. Offenders who leave prison have been found to be more vulnerable to suicide than the general population (Binswanger et al, 2007;Chapman et al, 2006;Kariminia et al, 2007;Butler, Jones, Kariminia, & Law, 2011;Henderson, Hobbs, Knuiman, Ridot, & Stewart, 2004) although one study has found released offenders to be equally as vulnerable to suicide as the general population (Brown, Krinsky, Lathrop, & Nolte, 2009). The first two weeks of release appear to be the most risky time for a suicide to occur (Binswanger et al, 2007;Kariminia et al, 2007).…”
Section: Recently Released Prisonersmentioning
confidence: 96%
“…Although they have not focused solely on community-sentenced offenders, these studies are helpful to highlight the problem of suicide in this population, as many of these offenders will still be supervised by the probation service. Offenders who leave prison have been found to be more vulnerable to suicide than the general population (Binswanger et al, 2007;Chapman et al, 2006;Kariminia et al, 2007;Butler, Jones, Kariminia, & Law, 2011;Henderson, Hobbs, Knuiman, Ridot, & Stewart, 2004) although one study has found released offenders to be equally as vulnerable to suicide as the general population (Brown, Krinsky, Lathrop, & Nolte, 2009). The first two weeks of release appear to be the most risky time for a suicide to occur (Binswanger et al, 2007;Kariminia et al, 2007).…”
Section: Recently Released Prisonersmentioning
confidence: 96%
“…However, many inmates with heroin addiction histories remain untreated in prison (Kastelic et al, 2008; Stover and Michels, 2010; Taxman et al, 2007). As a consequence, heroin addiction continues or resumes rapidly following release from incarceration (Dolan et al, 2007; Kinlock et al, 2011; Strang et al, 2006) and it contributes to high rates of HIV and hepatitis infection (Dolan et al, 2007; Kanato, 2008), overdose death among newly released inmates (Binswanger et al, 2011, 2012; Krinsky et al, 2009; Merral et al, 2010), increased criminal activity (Kinlock et al, 2003; Inciardi, 2008), and re-incarceration (Dolan et al, 2005; Metz et al, 2010). Thus, increased access to effective treatment interventions that begin during incarceration and continue in the community are needed for inmates with heroin addiction histories (Chandler et al, 2009; Dolan et al, 2007; Kinlock et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Department of Justice, 2012), and 700,000 are released annually (Travis 2005). People with a history of incarceration often have compromised health (Wang et al, 2009; Binswanger et al, 2011; Massoglia 2008) and post-incarceration mortality rates are higher than population mortality (Binswanger et al, 2007; Kariminia et al 2007; Stewart et al, 2004, Bird et al, 2003; Krinsky et al, 2009; Binswanger et al 2011; Merrall et al, 2010). …”
Section: Introductionmentioning
confidence: 99%